Extraction, characterization and microbiological evaluation of essential oils from commercial citrus waste (Research, Society and Development, 2021)
xWith the increase in the production of residues from food processing, several measures are being implemented generating benefits that go beyond environmental issues. This work proposed the reuse of surplus citrus fruit peels from commercial establishments, through the extraction of essential oils (OEs). Their antimicrobial efficacy, physical-chemical parameters, chemical constitution and the OE grouping patterns were evaluated based on statistical analyzes. The OEs were extracted from the shells by the hydrodistillation method. The refractive index, relative density and solubility in 90% ethanol were determined. The identification of the constituents was performed using GC-MS and for the groupings of the samples, PCA and HCA were used. For the antimicrobial activity, the disk diffusion technique was used, using two yeasts (Candida parapsilosis and Candida krusei) and two bacteria (Staphylococcus aureus and Escherichia coli). It was found that the OEs of orange cultivars have higher extraction yield and the physical-chemical analyzes were similar between orange and lemon cultivars. 61 components were identified in the OEs, with d-limonene being the majority. PCA and HCA revealed groupings that corroborate with the cultivars oranges, lemons and tangerines. All microorganisms were sensitive to the OEs of lemons and tangerine and E. coli was sensitive to all OEs. In turn, the bacterium S. aureus proved to be resistant to OEs from orange cultivars. It was found that the reuse of surplus citrus fruit peels is feasible, and OEs are effective against certain microorganisms.